2022
DOI: 10.47626/1516-4446-2022-2601
|View full text |Cite
|
Sign up to set email alerts
|

The moderation of multimorbidity and depressive symptoms on cognition

Abstract: Objective: Multimorbidity, or the occurrence of two or more chronic conditions, is a global challenge, with implications for mortality, morbidity, disability, and life quality. Psychiatric disorders are common among the chronic diseases that affect patients with multimorbidity. It is still not well understood whether psychiatric symptoms, especially depressive symptoms, moderate the effect of multimorbidity on cognition. Methods: We used a large (n=2,681) dataset to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…When we examined the association of multimorbidity patterns in diabetes patients with cognitive function, we found a “multisystem morbidity” class that consists of several chronic conditions, particularly depressive symptoms, is associated with declines in global cognitive function, which aligns with previous results ( de Araujo et al, 2022 ). In addition, we found that all patterns of multimorbidity in diabetes patients were associated with memory decline.…”
Section: Discussionsupporting
confidence: 87%
“…When we examined the association of multimorbidity patterns in diabetes patients with cognitive function, we found a “multisystem morbidity” class that consists of several chronic conditions, particularly depressive symptoms, is associated with declines in global cognitive function, which aligns with previous results ( de Araujo et al, 2022 ). In addition, we found that all patterns of multimorbidity in diabetes patients were associated with memory decline.…”
Section: Discussionsupporting
confidence: 87%
“…Zhang et al (2022) found that multimorbidity was associated with increased odds of having depressive symptoms (adjusted odds ratio of 1.51), and developing depressive symptoms (adjusted odds ratio of 1.65). Depression worsens the outcomes of people living with multimorbidity increasing disability, accelerating cognitive decay and also increasing costs in older individuals 5,7,29 . Moreover, depression was associated with a higher incidence of somatic disease, cardiometabolic disease, musculoskeletal diseases and digestive diseases in a 6-year follow-up cohort in the Netherlands 30 .…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that depression is associated with multimorbidity, the occurrence of two or more chronic diseases. It has been shown that the direction of this association seems to run from multimorbidity to depression 4,5 . As individuals age, they tend to become alone, losing friends and family members, which renders them susceptible to depressive symptoms 6 .…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to most chronic diseases sharing the same pathologic pathways 43 , 44 . Regardless, patients with mental health disorders have a higher risk of chronic disease development 48 such as dyslipidemia, obesity, and cardiovascular diseases 49 . Our finding emphasizes the need for a proper definition of multimorbidity which is not only the existence of two or more chronic diseases but also the clinically related pattern that connects one chronic disease to other diseases.…”
Section: Discussionmentioning
confidence: 99%